Epitranscriptomic investigation of myopia-associated RNA editing in the retina - Pan, Xu-Bin; He, Yu-Shan; Lu, Zijing; Pan, Hao-Ran; Wei, Zhi-Yuan; Jin, Yun-Yun; Wang, Jihong; Chen, Jian-Huan (Frontiers in Neuroscience, 2023)
Myopia is one of the most causes of vision loss globally, with an essential contribution from epigenetics. Adenosine-to-inosine (A-to-I RNA) editing is an epigenetic process involved in neurological disorders, yet its role in myopia remains undetermined. We performed a transcriptome-wide analysis of A-to-I RNA editing in the retina of form-deprivation myopia mice. Our study identified 91 A-to-I RNA editing sites in 84 genes associated with myopia. Notably, at least 27 of these genes with myopia-associated A-to-I RNA editing sites were found to be involved in myopia or related disease phenotypes in humans or animal models, such as very low-density lipoprotein receptor (Vldlr) in retinal neovascularization and hypoxia-induced factor 1 alpha (Hif1a) in myopia and scleral hypoxia. Moreover, functional enrichment showed that edited genes enriched in FDM were primarily involved in response to fungicides, a potentially druggable process for myopia prevention, and epigenetic regulation. In contrast, edited genes enriched in controls were the most involved in post-embryonic eye morphogenesis. Our results demonstrate altered A-to-I RNA editing associated with myopia in an experimental mouse model and warrant further study on its role in the molecular mechanism of myopia.